Assessing adherence and patient satisfaction with medication: Validation of TSQM in emerging markets. Issue 4 (12th September 2018) - Alam, Md. Moddassir; Sikdar, Pallab; Kumar, Amresh; Mittal, Arun
Abstract : Purpose: The study considers a four-construct model for validating the factors of overall patient satisfaction with medication. This paper aims to study the satisfaction of patients with their medication. Patient satisfaction with medication influences treatment-related behaviors, such as their possibility of continuing to use their medication, to take their medication correctly and to adhere with medication regimens. Design/methodology/approach: treatment satisfaction questionnaire for medication (TSQM) version 1.4 patient satisfaction model has been tested for reliability and validity through confirmatory factor analysis. A structured questionnaire, incorporating variables identified from original TSQM version 1.4 (Atkinson et al., 2005), has been used as a survey instrument for the study. Final respondent sample size was 380 patients who were on medication for a minimum duration of 10 days. Findings: In total, 75 per cent of the willingly participating patients were found to adhere to medication regimen as advised by their physician. Effectiveness, side effects, convenience and global satisfaction were found to be reliable and valid factors for assessing satisfaction with medication among patients in emerging market settings. Originality/value: The existing studies on measuring patient satisfaction have been majorly confined to developed economies. There is lack of focused research on patient satisfaction and its underlying determinants in the emerging market settings. The present study is an attempt to fill the existing research gap.